Strengthening Academic Literacy through a National Webinar on Strategies for Writing Scopus-Indexed Articles - Adi Isma; Amrang Amrang; Rahmatullah Syaripuddin; Fajriani Fajriani; Rusdiah Rusdiah; Ridwan Ridwan; Reski Reski; Ikhsan Ikhsan (PT. Global Research Collaboration, 2025)
Enhancing academic literacy remains a major challenge in promoting scientific publication productivity in Indonesia, particularly in internationally reputable journals such as Scopus. This article describes the implementation and evaluation of a national webinar entitled “Write It Right: Strategies for Writing Scopus-Indexed Scientific Articles,” organized by the English Education Study Program of Universitas Sulawesi Barat. The webinar aimed to strengthen the academic capacity of lecturers, students, and education practitioners in writing scientific articles that meet international standards. The event was conducted online via the Zoom Meeting platform on January 30, 2025, featuring experienced speakers in the field of international publication. A total of 407 participants registered, with 334 participants attending until the end of the session. The event evaluation was carried out through an online form, covering participants' satisfaction with the material, the speaker’s delivery, and the relevance of the content to their academic needs. The evaluation results indicated a high level of satisfaction, with most participants reporting that they gained practical insights and new motivation for writing scientific articles. Participant feedback also revealed that the webinar enhanced their understanding of scientific writing strategies and opened opportunities for future research collaboration. These findings underscore the importance of organizing online academic training as an effective strategy to strengthen the culture of scientific literacy within higher education institutions.